ANALISIS KINERJA KEUANGAN DENGAN MENGGUNAKAN RASIO LIKUIDITAS PADA PT. TELKOM INDONESIA Tbk - Alfin Akuba; Hasmirati Hasmirati (SIMAK, 2019)
The object of this research is at PT. Telkom Indonesia is listed on the Indonesia Stock Exchange. The research method used is a quantitative method because the research data is in the form of numbers and uses statistical analysis using liquidity ratios. Data analysis techniques use quantitative analysis in analyzing liquidity ratios, namely Current Ratio, Quick Ratio, Cash Ratio, At PT. Telkom Indonesia is listed on the Indonesia Stock Exchange for a period of three years (2015-2017) The results showed that PT. Telkom Indonesia Tbk for the period of three years 2015 to 2017 in terms of the company's current ratio and quick ratio has not been in accordance with the standard ratio. PT. Telkom Indonesia Tbk has fluctuating liquidity conditions so that this is still considered poor.